Features of the novel- essay “The phantom of the days that has not come” (Eurasian Journal of Philology Science and Education, 2022)
It is known that one of the genres of Kazakh literature, essays, appeared infrequently in the literature of the Soviet era. During the period of independence, within the framework of this genre, events and scenes in the Soviet space were described in detail, by the authors. Writers have used the rational side of the essay genre as a powerful way to analyze an idea in the context of artistic reality. The article analyzes a novel-essay from two books, which is the result of the relationship between the novel and the essay by the outstanding writer Kalikhan Yskak. He defines the features and poetic structure of the essay novel based on native literary criticism. The essay novel analyzes how the author writes very eloquently and with a peculiar style about the events he witnessed, as well as about his views and thoughts. Memoirs of Kalikhan Yskak about himself, about his time, about his contemporaries, about the environment in which he grew up, as well as the memories of the inhabitants of his native land, which were collected to create a wonderful piece of art, served as the basis for writing the article. It is argued that the novel-essay of the writer is distinguished by artistic language, poetic narration and a peculiar style. The concluding part says that the novel-essay of Kalikhan Yskak “The Ghost of the Days that Has Not Come” is a valuable work that has enriched Kazakh literature in artistic, genre, thematic, documentary and cognitive terms